2016
DOI: 10.2463/mrms.2014-0114
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-weighted MR Imaging of Deep Vein Thrombosis

Abstract: Magnetic resonance (MR) imaging is not commonly used as a diagnostic tool for deep vein thrombosis (DVT). Technological advances in fat saturation pulse sequences and surface coils have enabled the application of diffusion-weighted imaging (DWI) to whole-body imaging, 1 and we applied this technique to detect DVT and evaluated its tissue contrast.To evaluate the extent of DVT in a 60-year-old woman with asymptomatic pulmonary thromboembolism, we performed noncontrast diffusion and T 1 -weighted MR imaging (T 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 3 publications
1
0
0
Order By: Relevance
“…17 We also reported that DWI detected DVT as a region of high SI in a symptomatic patient. 18 The present findings are consistent with these previous reports. Favrole et al found high SI on DWI in 41% of patients with recent cerebral venous thrombosis and no high SI in any thrombi on follow-up MRI.…”
Section: Discussionsupporting
confidence: 94%
“…17 We also reported that DWI detected DVT as a region of high SI in a symptomatic patient. 18 The present findings are consistent with these previous reports. Favrole et al found high SI on DWI in 41% of patients with recent cerebral venous thrombosis and no high SI in any thrombi on follow-up MRI.…”
Section: Discussionsupporting
confidence: 94%